2020
DOI: 10.1111/csp2.272
|View full text |Cite
|
Sign up to set email alerts
|

Strategic advertising of online news articles as an intervention to influence wildlife product consumers

Abstract: Changing human behavior is essential for biodiversity conservation, but robust approaches for large scale change are needed. Concepts like repeat message exposure and social reinforcement, as well as mechanisms like online news coverage and targeted advertisements, are currently used by private and public sectors, and could prove powerful for conservation. Thus, to explore their potential in influencing wildlife consumption, we used online advertisements through Facebook, Google, and Outbrain, to promote news … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…Research has shown that species conservation awareness can increase the intended willingness of consumers to accept substitutions for medicinal products that are normally derived from wild animals, which could drive social marketing and stakeholder engagement efforts in the future (Liu et al., 2016). Further, in a behaviour change intervention in Singapore, saiga horn consumers learning about the saiga's conservation status through news promotions commonly responded by asking about or sharing CMM substitutes (Doughty et al, 2020).…”
Section: A Better Understanding Of Tcm: Implications For Conservationmentioning
confidence: 99%
“…Research has shown that species conservation awareness can increase the intended willingness of consumers to accept substitutions for medicinal products that are normally derived from wild animals, which could drive social marketing and stakeholder engagement efforts in the future (Liu et al., 2016). Further, in a behaviour change intervention in Singapore, saiga horn consumers learning about the saiga's conservation status through news promotions commonly responded by asking about or sharing CMM substitutes (Doughty et al, 2020).…”
Section: A Better Understanding Of Tcm: Implications For Conservationmentioning
confidence: 99%
“…Using the intervention approach developed through the design process in this text, we carried out the next steps in the intervention: (a) identifying applicable behaviour change techniques; (b) conducting thorough testing of selected technique components; and (c) implementing and evaluating the intervention (Doughty et al., 2020; Doughty et al, in press). These steps enabled us to assess whether the assumptions we had made about these influences on our target audience held, and whether the intervention based on these assumptions did in fact induce a desired change.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, this approach was then refined into an intervention plan: the use of targeted online advertising to promote news articles about saiga horn in Singapore (Doughty et al., 2020). This plan drew on literature around the influence of repeated message exposure, social reinforcement, and news coverage, as well as a second set of focus groups, where we could test components such as which news outlets our target audience preferred.…”
Section: Populating the Design Process (Steps 5–7)mentioning
confidence: 99%
See 2 more Smart Citations